Prevention of incisional hernia after midline laparotomy with prophylactic mesh reinforcement: a meta-analysis and trial sequential analysis. Issue 3 (14th February 2020) - Jairam, A P; López-Cano, M; Garcia-Alamino, J M; Pereira, J A; Timmermans, L; Jeekel, J; Lange, J; Muysoms, F
Abstract: Background: Incisional hernia is a frequent complication after abdominal surgery. The aim of this study was to assess the efficacy of prophylactic mesh reinforcement (PMR) after midline laparotomy in reducing the incidence of incisional hernia. Methods: A meta-analysis was conducted following PRISMA guidelines. The primary outcome was the incidence of incisional hernia after follow-up of at least 12 months. Secondary outcomes were postoperative complications. Only RCTs were included. A random-effects model was used for the meta-analysis, and trial sequential analysis was conducted. Results: Twelve RCTs were included, comprising 1815 patients. The incidence of incisional hernia was significantly lower after PMR compared with sutured closure (risk ratio (RR) 0·35, 95 per cent c.i. 0·21 to 0·57; P < 0·001). Both onlay (RR 0·26, 0·11 to 0·67; P = 0·005) and retromuscular (RR 0·28, 0·10 to 0·82; P = 0·02) PMR led to a significant reduction in the rate of incisional hernia. The occurrence of seroma was higher in patients who had onlay PMR (RR 2·23, 1·10 to 4·52; P = 0·03). PMR did not result in an increased rate of surgical-site infection. Conclusion: PMR of a midline laparotomy using an onlay or retromuscular technique leads to a significant reduction in the rate of incisional hernia in high-risk patients. Individual risk factors should be taken into account to select patients who will benefit most. [Correction added on 19 February 2020, after first online publication: J. García Alamino has been amended to J. M. Garcia-Alamino] Graphical Abstract: Prophylactic mesh reinforcement of a midline laparotomy leads to a significant reduction in the rate of incisional hernia in high-risk patients, for both onlay and retromuscular mesh reinforcement. Mesh high risk patients